Caracterização dos depósitos glaciais permo-carbonífero no sul de Minas Gerais, Brasil: Formação Aquidauana ou Grupo Itararé? - Araújo, Bruno Cesar [UNESP] (2013)
The Itararé Group records glacial events that took place on the Gondwana Paleocontinet during Carboniferous and Permian periods. Rocks from this unit crop out at the eastern / southeastern part of the Paraná Basin (South and Southeast regions of Brazil). The Aquidauana Formationis chrono-correlated to the Itararé Group and crops out at the western margin of the Paraná Basin, where its type section was described. The occurrence of the Aquidauana Formation is also documented in the Southern Minas Gerais State, extending southward to the Mogi-Guaçu river valley in the São Paulo State. Both units have similar lithotypes and their colors are the main distinguishing factor. Rocks from the Itararé Group are predominantly beige / whitish-gray and rocks from the Aquidauana Formation are reddish-brown. The contact, or transition, between these units is yet poorly understood. According to the geologic maps available for the São Paulo State this transition is abrupt, and spatially marked by the Mogi-Guaçu river. Rocks from the Aquidauana Formation crop out on the right bank (north) and the Itararé Group on the left (south). The present dissertation aims to characterize the Aquidauana Formation (Itararé Group) in the southern Minas Gerais State and contribute to the discussion about its formation and the origin of the red coloration of the rocks. Paleogeographic data corroborate previous studies and indicate the occurrence of alluvial fan sand braided rivers systems, both under the influence of glacial conditions, showing outwash and lacustrine deltas deposits. Petrographic studies suggest that the red dish coloration of Aquidauana Formation rocks is associated with the diagenetic evolution, since a thin layer of Fe-oxide is coating overgrown grains. This process is interpreted to be associated with exposure of this unit, supported by the unconformity between Aquidauana Formation and superimposed units (Tatuí, Pirambóia and Botucatu formation